2018
DOI: 10.1253/circj.cj-18-0390
|View full text |Cite
|
Sign up to set email alerts
|

Surgical as Opposed to Transcatheter Aortic Valve Replacement Improves Basal Interventricular Septal Hypertrophy

Abstract: Objectives. Basal interventricular septal (IVS) hypertrophy (BSH) with reduced basal IVS contraction and IVS to aorta angle is frequently associated with aortic stenosis (AS). The shape of BSH suggests compression from longitudinally elongated ascending aorta, causing basal IVS thickening and contractile dysfunction, which further suggests the possibility of aortic wall shortening to improve the BSH. Surgical aortic valve replacement (SAVR), as opposed to transcatheter AVR (TAVR), includes aortic wall shorteni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…This reverse remodeling has already been reported, as Yoshitani et al showed a significant decrease in IVS thickness following aortic valve replacement surgery. 43 The finding regarding the AF group is in line with the previously described pathophysiology, as left atrial pressure is closely related to left ventricle filling pressure, and the latter with IVS thickness. 44 A study by Shah et al found a higher AF recurrence rate following rhythm control strategy in patients presenting with left ventricle hypertrophy.…”
Section: Discussionsupporting
confidence: 88%
“…This reverse remodeling has already been reported, as Yoshitani et al showed a significant decrease in IVS thickness following aortic valve replacement surgery. 43 The finding regarding the AF group is in line with the previously described pathophysiology, as left atrial pressure is closely related to left ventricle filling pressure, and the latter with IVS thickness. 44 A study by Shah et al found a higher AF recurrence rate following rhythm control strategy in patients presenting with left ventricle hypertrophy.…”
Section: Discussionsupporting
confidence: 88%
“…The importance of USH has been reported many times. 5,19,20 The present study also demonstrated the important role of USH in causing increased LVOT VTI, contributing to discrepant AVAIs, and recon-…”
Section: Study Limitationssupporting
confidence: 60%
“…Sigmoid septum, which is one of the causes of left ventricular outflow tract (LVOT) obstruction [49], is a non-uniform pattern of hypertrophy in which basal intervetricular septum (IVS) shows a graeter degree of thickening than other regions, and is also characterized by a diminished angle between the basal IVS and the aorta [50][51][52]. Sigmoid septum is incidentally found in patients with older age and hypertension by echocardiography, and basically considered to be of little clinical importance, with a relatively benign prognosis [51][52][53][54]. Because AS develops mainly in the aged population, sigmoid septum is also common in patients with AS.…”
Section: Sigmoid Septummentioning
confidence: 99%
“…Though the mechanism of the formation of sigmoid septum has not been established yet, Yoshitani et al reported that augmented compression by longitudinally elongated ascending aorta to the interventricular septum may cause sigmoid septum, and that the shortening of the elongated ascending aorta could improve sigmoid septum. In this paper, they focused on the shortening of the ascending aorta by aortatomy and suturing in SAVR, which was not performed in TAVR, and found that SAVR as opposed to TAVR improves the interventricular septumaorta angle, basal interventricular septum thickness and its functional impairment [51].…”
Section: Sigmoid Septummentioning
confidence: 99%
See 1 more Smart Citation